MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA KESEHATAN - Mansyur Mansyur (Universitas Borneo Tarakan, 2020)
AbstractHealth services to vulnerable communities cause health disputes between health care providers such as hospitals, doctors / dentists and nurses with patients or their families. Health dispute resolution can be done through the court either through criminal justice or civil court. Beside that, the dispute of health dispute can also be done through mediation institution Mediation institution as an alternative dispute of health disputes if it meets the following criteria: Health disputes related to health services received or directly related to the patient, Health disputes included in the category of medical discipline violation Not included as a crime, and based on the will of the parties to choose a mediation institution as an attempt to resolve the dispute and be done with good faith. The result of the parties' agreement is set forth in a written certificate of having a binding force as an agreement for the parties .. and shall be registered in the District Court by filing a lawsuit to be stipulated in the peace certificate by the local District Court judge. Keywords; Mediation, Dispute, Health